Spirocercosis in a dog - Toledo, Cristina Madelein; Fuentes, Kevin Berrios; Rivera, Junior Raxa Chavarría; Gómez, Ervin Antonio Cano; Rimoldi, Mario Guillermo; Carvallo, Francisco (Brazilian Journal of Veterinary Pathology, 2025)
An adult female mixed breed dog was found in a local street market and taken to an animal rescue center. A hemogramon the day of arrival revealed anemia, lymphopenia, as well as thrombocytosis and neutrophilia. The patient received prophylactictreatment with praziquantel, febendazole, toltrazuril, and doxycycline, but died 6 days after arrival.